2009
DOI: 10.1124/dmd.108.022814
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Occupancy and Brain Free Fraction

Abstract: ABSTRACT:This study was designed to investigate whether brain unbound concentration (C u,brain ) is a better predictor of dopamine D 2 receptor occupancy than total brain concentration, cerebrospinal fluid concentration (C CSF ), or blood unbound concentration (C u,blood ). The ex vivo D 2 receptor occupancy and concentration-time profiles in cerebrospinal fluid, blood, and brain of six marketed antipsychotic drugs were determined after oral administration in rats at a range of dose levels. The C u,brain was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 13 publications
0
67
0
Order By: Relevance
“…There are several reports based on Mdr1a KO models demonstrating that Pgp reduces risperidone uptake into the brains of both mice (Wang et al, 2004;Doran et al, 2005;Summerfield et al, 2006) and rats (Bundgaard et al, 2012). Using plasma and brain homogenate free fraction analysis, efflux asymmetry was observed in mice (Mau- (Watson et al, 2009). In a study involving direct measurement by microdialysis of risperidone in brain ECF of rats and comparison to unbound plasma concentrations after intravenous infusion over 6 h, Liu et al (2009) reported a risperidone steady-state ECF-to-plasma ,u ratio of 0.53.…”
Section: Compartmental Pk Parameter Estimates Based On Simultaneous Fmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports based on Mdr1a KO models demonstrating that Pgp reduces risperidone uptake into the brains of both mice (Wang et al, 2004;Doran et al, 2005;Summerfield et al, 2006) and rats (Bundgaard et al, 2012). Using plasma and brain homogenate free fraction analysis, efflux asymmetry was observed in mice (Mau- (Watson et al, 2009). In a study involving direct measurement by microdialysis of risperidone in brain ECF of rats and comparison to unbound plasma concentrations after intravenous infusion over 6 h, Liu et al (2009) reported a risperidone steady-state ECF-to-plasma ,u ratio of 0.53.…”
Section: Compartmental Pk Parameter Estimates Based On Simultaneous Fmentioning
confidence: 99%
“…In Mdr1a mouse KO studies , clozapine brain concentrations were increased in KO relative to WT animals, but the drug was unlike risperidone in strongly differentiating as a Pgp substrate. In addition, no support for clozapine net efflux asymmetry was obtained using plasma and brain free fraction analysis in mice (Maurer et al, 2005) or rats (Watson et al, 2009). Clinical studies have shown a relationship between Mdr1a polymorphisms and efficacious clozapine systemic exposure (Jaquenoud Sirot et al, 2009;Consoli et al, 2009).…”
Section: Compartmental Pk Parameter Estimates Based On Simultaneous Fmentioning
confidence: 99%
“…Therefore, total brain concentration does not represent the drug concentration at the biophase. Although the scientific rationale for the free drug hypothesis is very strong, there are limited data in the literature to actually prove that the unbound brain concentration, not the total brain tissue concentration, determines CNS activity (Cox et al, 1998;Kalvass et al, 2007b;Watson et al, 2009). Because of the lack of extensive well documented data in the literature and the lack of understanding of novel drug targets in most drug discovery and development programs, sometimes it is debatable whether the unbound brain concentration or the total brain concentration determines in vivo activity.…”
mentioning
confidence: 99%
“…This is because of factors related to CSF turnover, intrabrain diffusion, extra-intracellular exchange, and qualitative and quantitative differences in BBB and blood-CSF-barrier transport mechanisms. Because many targets (receptors) face the brain extracellular fluid (ECF), brain ECF concentrations are anticipated to reflect target site concentrations best and will therefore provide a better basis to describe PK and pharmacodynamic (PD) relations in a more mechanistic manner (Del Bigio, 1995;de Lange et al, 1999de Lange et al, , 2005de Lange and Danhof, 2002;Watson et al, 2009;Jeffrey and Summerfield, 2010).…”
Section: Introductionmentioning
confidence: 99%